Corpus-based teaching materials for incorporating corpus literacy into German as a foreign language classes - Sökefeld, Carla; Stulen, Anastasiia (Kalbotyra, 2025)
While the discussion of using corpora in language learning was long focused on English as a foreign language, recently, there has been an increase in publications dealing with the benefits of employing corpora for German as a foreign language as well. Corpus-based work has been shown to benefit language learning. From the perspective of philological study programs, it is moreover beneficial to strengthen students’ corpus literacy needed throughout their studies by already integrating corpus work into language courses. This paper presents a set of teaching materials: Corpus-based exercises on frequent word combinations and the DWDS-Wortprofil as well as corpus-linguistic “cheat-sheets”, i.e., glossaries with explanations of common corpus-linguistic terms. The way the materials are designed is intended to alleviate students’ (and teachers’) inhibitions when it comes to integrating corpus work into German as a foreign language classes. The teaching materials were developed in the context of the “German Studies Institute Partnership” funded by the DAAD between Vilnius University and the University of Hamburg and strive to combine three learning areas vital for German Studies abroad: German as a foreign language skills, linguistic knowledge, and corpus literacy. There are several pitfalls concerning the successful implementation of corpus work into German classes, e.g., the mutability of online corpora and corpus tools, which are addressed in this paper. An initial piloting of the materials shows that especially differing uses in terminology between corpus tools and textbooks are challenging to students. Nevertheless, this paper argues that incorporating corpus-based exercises into language classes is beneficial to building a foundation for students’ corpus literacy to be expanded throughout their philological studies.